History of the secularization of the public powers and the Western Law-Policy-Protocol relations (Journal of the Sociology and Theory of Religion, 2021)
This is a revisionist study (in a critical-comparative & hermeneutic way), under an interdisciplinary approach (mixing Politics, Law, Protocol & Religion), which removes confusion veils and it helps to (re)evaluate the development of Western secularization in the relations sacred-profane, by the recovery and the reinterpretation of official sources and its institutional monitorization. It is clarified the transition from Old Regime to New Regime and the relational models applied.
Keywords: Western; power; sacred; profane; secularization; liberty.